Human Articular Chondrocytes Express Multiple Gap Junction Proteins: Differential Expression of Connexins in Normal and Osteoarthritic Cartilage - Mayan, Maria D. (American Society for Investigative Pathology, 2013)
Osteoarthritis (OA) is the most common joint disease and involves progressive degeneration of articular cartilage. The aim of this study was to investigate if chondrocytes from human articular cartilage express gap junction proteins called connexins (Cxs). We show that human chondrocytes in tissue express Cx43, Cx45, Cx32, and Cx46. We also find that primary chondrocytes from adults retain the capacity to form functional voltage-dependent gap junctions. Immunohistochemistry experiments in cartilage from OA patients revealed significantly elevated levels of Cx43 and Cx45 in the superficial zone and down through the next approximately 1000 μm of tissue. These zones corresponded with regions damaged in OA that also had high levels of proliferative cell nuclear antigen. An increased number of Cxs may help explain the increased proliferation of cells in clusters that finally lead to tissue homeostasis loss. Conversely, high levels of Cxs in OA cartilage reflect the increased number of adjacent cells in clusters that are able to interact directly by gap junctions as compared with hemichannels on single cells in normal cartilage. Our data provide strong evidence that OA patients have a loss of the usual ordered distribution of Cxs in the damaged zones and that the reductions in Cx43 levels are accompanied by the loss of correct Cx localization in the nondamaged areas.